LEADERSHIP AND POLICY TRANSFORMATION IN MOBILE LIBRARY SERVICES: A CASE STUDY OF UPT PERPUSTAKAAN PROKLAMATOR BUNG KARNO - Citra Kartika Sari; Martutik Martutik; Rani Auliawati Rachman (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
The mobile library service at UPT Perpustakaan Proklamator Bung Karno has shifted its focus from reaching public facilities to primarily serving schools. This transformation raises critical questions about how leadership influences policy implementation and how such orientation affects service inclusivity and public access. This study aims to analyze the role of leadership in shaping and implementing mobile library policies under institutional and resource constraints. A qualitative case study approach was employed to explore leadership orientation, internal communication, and implementer initiative. Data were collected through semi-structured interviews, direct observations, and documentation, and analyzed using Miles, Huberman, and Salda